(untitled) (The Strategic Review for Southern Africa, 2020)
This, the second edition of the 40th volume of the Strategic Review, straddles a number of these above-mentioned focal areas regional security, epistemological shifts and state making. A number of articles in this edition come from the 2017 Limpopo/Gauteng Colloquium of the South African Association of Political Studies hosted by the Universities of Limpopo and Venda through the able hands of Dr Kgothatso Shai (UL) and Prof Richard Molapo (UNIVEN), and with the generous support of the National Institute for Social Science and Humanities. While most of the articles focus on the geographic area called southern Africa, two articles discuss issues that do not emanate from this area, but whose article on migration and terrorism draws from the experience of West Africa, but its insights should attract the attention of southern Africanists already worried about the rise of terrorism in Mozambique and on the Indian Ocean coast generally. Its arguments about the role of networks, inter-linkages of various kinds and globalisation-induced migration as factors in the changing nature and character of terrorism may help southern African anticipate what seems to be an emerging terror factor in its regional conflict theatre.